2016
DOI: 10.1007/s10461-016-1332-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV Among U.S. Female Sex Workers: Systematic Review and Meta-analysis

Abstract: Although female sex workers are known to be vulnerable to HIV infection, little is known about the epidemiology of HIV infection among this high-risk population in the United States. We systematically identified and critically assessed published studies reporting HIV prevalence among female sex workers in the United States. We searched for and included original English-language articles reporting data on the prevalence of HIV as determined by testing at least 50 females who exchanged sexual practices for money… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 39 publications
1
67
1
1
Order By: Relevance
“…Although HIV prevalence among women who exchanged sex in our study is lower than that reported in a systematic review of US studies among female sex workers (17.3%), 23 most studies in that review were conducted in the 1990s. Furthermore, our findings may not be directly comparable as all women in our sample injected drugs and 60% only exchanged sex with a single partner.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Although HIV prevalence among women who exchanged sex in our study is lower than that reported in a systematic review of US studies among female sex workers (17.3%), 23 most studies in that review were conducted in the 1990s. Furthermore, our findings may not be directly comparable as all women in our sample injected drugs and 60% only exchanged sex with a single partner.…”
Section: Discussioncontrasting
confidence: 85%
“…A recent systematic review documented only 14 studies in the United States that reported HIV prevalence among sex workers, with estimates ranging from 0.3% to 30% and an average prevalence of 17.3% [95% confidence interval (CI): 13.5% to 21.9%]. 23 Most are decades old, only 3 present data beyond a single city or state, and the majority used convenience sampling. Findings regarding HIV prevalence specifically among women who inject drugs are inconsistent: A longitudinal case–control study among PWID in San Francisco found that women who traded sex for money in the past year were 5.1 times more likely to become HIV infected, 8 whereas other studies among PWID have found that exchange sex was not associated with being HIV positive, 24 or that this association was only seen for women with large numbers of partners.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with other women in low- and middle-income countries (LMIC), FSW were found to be 13.5 times more likely to be living with HIV infection [5]. The overall HIV prevalence among FSW was found to be 11.8% in LMIC and 17.3% in the US as a high-income country [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Paz-Bailey et al [17] reported HIV prevalence of 17.3% among adult female sex workers in US. Magnani et al [18] reported prevalence of among direct and indirect FSW in Indonesia as 10.5% and 4.9% respectively (HIV), 35.6% and 28.7% respectively (chlamydia), 31.8% and 14.3% respectively (gonorrhea) and 7.3% and 3.5% respectively (active syphilis).…”
Section: Resultsmentioning
confidence: 99%